INTEPRETASI HAKIM DALAM MEMUTUS PERKARA PERCERAIAN BERDASARKAN ALASAN “PERTENGKARAN SECARA TERUS MENERUS DAN TIDAK ADA HARAPAN UNTUK HIDUP RUKUN LAGI" - Khadijah, Siti; Hariman, Hariman; Renata, Renata; Sufiarina, Sufiarina (Indonesia of Journal Business Law, 2025)
This study examines judges' interpretations in deciding divorce cases based on the grounds of “continuous disputes” and “no hope of living harmoniously anymore.” These reasons are often used as legal bases by plaintiffs or defendants in divorce proceedings in Indonesia, as stipulated in Article 39 paragraph (2) of Law Number 1 of 1974 on Marriage and Article 19 letter (f) of Government Regulation Number 9 of 1975. The study aims to analyze how judges interpret these terms within the context of law and facts presented during trials. The research specifications used in this study are descriptive analysis, namely describing the facts in detail about the object of research so that problems are found in the form of inconsistencies between applicable regulations and practices that occur in the field, then trying to analyze and find a way out of a problem. This research is a normative legal research supported by empirical, namely research that continues to emphasize secondary data accompanied by taking samples of empirical data as implementation practices in the field. Secondary data consists of primary legal materials and secondary legal materials. The way to obtain data in this study is by conducting a study of library materials in the form of legal literature and legislation. After the data is collected, it is then analyzed using a qualitative legal method, which is closely related to the type of research categorized as normative legal research whose approach is more abstract-theoretical. The research findings indicate that judges' interpretations are based on evidence submitted by the parties, such as witness statements, documentary evidence, and facts about marital life revealed during the proceedings. “Continuous disputes” are defined as recurring conflicts that remain unresolved despite efforts for mediation or peaceful resolution. Meanwhile, “no hope of living harmoniously anymore” refers to a marital relationship that has become disharmonious and irreparable based on solid evidence. In making decisions, judges also consider principles of justice, the welfare of children (if any), and the impact of divorce on the parties involved. The study concludes that judges’ interpretations are dynamic and highly case-specific, requiring a comprehensive approach to ensure that rulings address legal, social, and moral aspects appropriately.